Differential effect of anticoagulation therapy in patients older versus younger than 80 years with atrial fibrillation and severe chronic kidney disease. (25th November 2020) - Fortuny Frau, E; Raposeiras-Roubin, S; Andreu-Cayuelas, J.M; Garcia-Egido, A; Ortiz-Cortes, C; Camacho-Freire, S.J; Alonso, P; Jorge-Perez, P; Lopez-Pais, J; Bravo-Marques, R; Palacios-Rubio, J; Benezet-Mazuecos, J; et al.
Abstract: Introduction: In non-valvular atrial fibrillation (NVAF) patients, advanced age and chronic kidney disease (CKD) raise the thrombotic and bleeding rates, making the decision of antithrombotic therapy a challenge. Therefore, we conducted an analysis to explore the efficacy and safety of anticoagulation therapy in this population (AF patients ≥80 years) in comparison with younger AF patients (<80 years). Methods: For these results we have analyzed data from FIBRA, a multicentric Spanish retrospective registry on patients with CKD-EPI <30 ml/min/1.73 m 2 and newly diagnosed NVAF. For death, multivariable Cox regression analysis was developed. For embolic and bleeding events, competing-risks regression based on Fine and Gray's proportional subhazards model was performed, being death the competing event Results: We analyzed 405 patients with CKD-EPI <30 ml/min/1.73 m 2 . 232 were ≥80 years-old (57.3%). Median of CHA2DS2-VASC and HASBLED scores were 5 and 3 in patients ≥80 years, respectively, and 3 and 2 in patients <80 years, respectively. The prescription of antithrombotic therapies in elderly versus younger patients is shown in Figure 1. During a follow-up of 4.6±2.5 years, 205 died (50.6%), 34 had embolic events (8.4%) and 85 had bleeding outcomes (21.0%). After multivariate analysis, no benefit of anticoagulation therapy was found for mortality in both, older and younger patients. In patients ≥80, anticoagulation was associated with higher rates of bleeding events without a decrease in embolic outcomes. Conclusion: In our registry, anticoagulation has not shown benefit in NVAF patients ≥80 years with glomerular filtrate rate <30 ml/min/1.73 m 2, increasing the risk of bleeding events without reducing embolic outcomes. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): BMS-Pfizer alliance unconditional grant